PERILAKU DAN PENGETAHUAN MASYARAKAT TERHADAP PENERAPAN 5M (MEMAKAI MASKER, MENCUCI TANGAN, MENJAGA JARAK, MENJAUHI KERUMUNAN, MENGURANGI MOBILISASI) DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN 5M UNTUK MENCEGAH PENULARAN VIRUS COVID-19 - Damayanti, Shella; Afiyanti, Yati; Faridah, Ida (Nusantara Hasana Berdikari, 2022)
Corona virus or covid-19, this virus infects the respiratory tract which causes patients with high fever, cough, runny nose and shortness of breath. Recently, research has found new symptoms, namely attacking the digestive system which causes diarrhea, nausea and vomiting. On March 2, 2020 as many as 12,776 and 930 cases of death were reported in 34 provinces of Indonesia. On March 19, 2020 as many as 214,894 people were infected with the corona virus or covid-19, around 8,732 people died and 83,313 people recovered from the corona virus or covid-19. Covid-19 transmission through doplet such as from person to person or direct contact with sufferers. Various efforts have been made to reduce the transmission of the covid-19 virus, one of which is increasing healthy living and by carrying out the 5M movement (Wearing Masks, Washing Hands, Keeping Distance, Crowds, and Limiting Mobilization) and maintaining body immunity (Kemenkes RI, 2020). Methods: This research uses descriptive correlation with Cross-Sectional Design approach. In this study, the technique of collecting samples used total sampling with a total of 180 Indonesian respondents. In this study, it is used to test the statistic using the chi square test. Results: The results of the Chi Square test obtained a p-value of 0.001 < 0.001 which means that there is a relationship between knowledge and behavior with the supporting factors. Conclusion: There is a significant relationship between knowledge and behavior of the community towards the implementation of 5M and its supporting factors.